2011
DOI: 10.1007/s10750-011-0884-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between genetic, chemical, and bacterial diversity in the Atlanto-Mediterranean bath sponge Spongia lamella

Abstract: Does diversity beget diversity? Diversity includes a diversity of concepts because it is linked to variability in and of life and can be applied to multiple levels. The connections between multiple levels of diversity are poorly understood. Here, we investigated the relationships between genetic, bacterial, and chemical diversity of the endangered Atlanto-Mediterranean sponge Spongia lamella. These levels of diversity are intrinsically related to sponge evolution and could have strong conservation implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
1
15
1
Order By: Relevance
“…In this study, we observed metabolomic differences between sampling sites, which were not dependent on the geographic scale studied (10 km compared to > 100 km). However, the spatial scale studied remains considerably small, and thus larger geographical scales should be studied to assess distance decay in chemical fingerprint similarities (Noyer and Becerro 2012;Noyer et al 2011). Other factors that could participate to spatial variations are biotic interactions (De Caralt et al 2013) and the variable part of the sponge metabolome (Borchert et al 2016;Schmitt et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed metabolomic differences between sampling sites, which were not dependent on the geographic scale studied (10 km compared to > 100 km). However, the spatial scale studied remains considerably small, and thus larger geographical scales should be studied to assess distance decay in chemical fingerprint similarities (Noyer and Becerro 2012;Noyer et al 2011). Other factors that could participate to spatial variations are biotic interactions (De Caralt et al 2013) and the variable part of the sponge metabolome (Borchert et al 2016;Schmitt et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the Mediterranean populations of the introduced calcareous sponge Paraleucilla magna, clonality was found to be almost inexistent (C asex = 1.5%, Guardiola et al, 2011). No clonality was reported in the genetic studies of the Mediterranean bath sponges S. officinalis (Dailianis et al, 2011) and S. lamella (= S. agaricina ) (Noyer, 2010), which is accordance with the lack of asexual buds and the unbreakable (elastic) consistence of the two species, which makes fragmentation unlikely.…”
Section: Asexual Propagules Have Been Reported In Representatives Of mentioning
confidence: 91%
“…The population genetics of two emblematic Mediterranean bath sponges has been studied recently by microsatellites. Seven populations along the western Mediterranean and the Portugal coasts of Spongia lamella were analyzed by using seven microsatellite loci (Noyer, 2010). Inbreeding was the main characteristic for all loci and populations, which was attributed to mating among relatives or to the existence of breeding subunits within populations.…”
Section: Genetic Differentiation At Large and Regional Geographical Smentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that these variations may have been due to both genetic and environmental factors. A further study on S. lamella revealed that the populations from the five regions (Portugal, Gibraltar, Baleares, Catalonia, and South France) significantly differed within their genetic and chemical diversity as well as their associated bacteria (Noyer and Becerro 2012). Similarly, Rohde et al (2012) found different metabolites and compound concentrations in the tropical sponge Stylissa massa across different ocean basins and within sites.…”
Section: Marine Chemical Ecology: Predator-prey Interactions and Compmentioning
confidence: 95%